Using gravel for environmental enrichment in salmonid hatcheries: The effect of gravel size during egg incubation, endogenous and first feeding in rainbow trout. (17th February 2019) - Reiser, Stefan; Pohlmann, Dominique Marie; Koops, Udo; Gröger, Joachim Paul; Focken, Ulfert
Abstract: Environmental enrichment aims for a deliberate increase in structural complexity in otherwise plain rearing units, helping to reduce aberrant traits and promote welfare of fish kept in captivity. Before putting enrichment protocols into practice, however, practitioners like hatchery managers need clear guidelines on enrichment measures and on the substrates used. In the present study, we used rainbow trout as a model species for salmonid rearing and investigated the use of a single layer of three different gravel types, i.e., small (4–8 mm), medium (8–16 mm) and large (16–32 mm), for environmental enrichment during egg incubation, endogenous and first feeding of rainbow trout and compared this to a barren control. From the egg stage onwards, we determined mortality, fungal prevalence as well as growth of larvae and fingerlings. We found that gravel size significantly affected mortality and fungal prevalence with the smallest gravel size and the control showing the lowest incidents. Growth of larvae and fingerlings was not affected by gravel, both when compared between gravel types and to the barren control. When using gravel for environmental enrichment in salmonid hatcheries, a small gravel size should be used. Small gravel provides the fish with a more natural environment without compromising practical feasibility of enrichment in hatcheries, still allowing for easy visual inspection and manual control of the reared fish.